Performance enhancement, life cycle assessment, and feature analysis of wheat starch-based NaCl-binder as a sustainable alternative to OPC mortar - Mohammad Reza Hanafi; Hamed Rahimpour; Sahar Zinatloo-Ajabshir; Faramarz Moodi; Ahmad Fahmi (Results in Engineering)
The primary aim of this investigation is to advance the properties of an innovative and sustainable wheat starch-based NaCl-binder (WSB) material. The scope encompasses the material's ecological and structural applications and potential for paving usage. The creation of hydrophobic and environmentally friendly WSB samples under microwave curing conditions was achieved by using a salt mortar with varying sizes of salt grains, water, and wheat starch as a binding agent. This study investigated the effects of curing time, water and starch amounts, and salt particle size on strength, modulus of rupture, and modulus of elasticity. Additionally, XRD, XRF, and SEM analyses were carried out to assess the chemical characteristics of WSB and the bonding between its particles. The mix design with the highest compressive strength, which consisted of 1 wt% starch, 8 min of microwave treatment, and 10 wt% water, attained a strength of 25.27 MPa. Furthermore, coconut oil was employed to effectively make the samples water-resistant. Following different guidelines, WSB could be categorized as structural concrete and utilized for structural and paving bricks. A vital aspect of this study is the exceptional environmental performance of WSB as a structural material, highlighting its originality and importance.